PROTOTIPE PENGONTROL SMART DOORBELL BERBASIS TELEGRAM - Sakia, Sakia; Farida, Farida; Iryani, Juniarti (CV. LAJAGOE PUSTAKA, 2023)
Abstract This study aims to: (1) Design a Telegram-Based Smart Doorbell Controller Prototype. (2) Find out the implementation of a Telegram Based Smart Doorbell Controller Prototype in the house of resident at Ponre, Matekko Village, Gantarang District, Bulukumba Regency. This study used the R&D research method, namely by comparing previous research so that the research carried out was even better. R&D research has several stages, namely: (1) analysis stage. (2) Design stages. (3) Development stages. (4) Stages of testing. And (5) report stages. The results of this study indicate that: (1) Telegram-based smart doorbell controller prototypes were made or designed using Esp32 Cam, Push Buttons, Df Mini Player, Memory, Speakers, Relays, Selenoids, Servo Motors, Android Smartphones, Telegram Applications, Wifi, and 12V adapter. (2) implementation of the telegram-based smart doorbell controller prototype which was carried out at the house of a resident in Ponre, Ponre, Matekko Village, Gantarang District, Bulukumba Regency. When someone visits the house and then presses the bell, it can emit a sound that has been entered into the df mini player's memory such as